PENGATURAN TANAH BENGKOK DI DESA SOJOPURO KABUPATEN WONOSOBO BERDASARKAN UNDANG-UNDANG NO. 6 TAHUN 2014 TENTANG DESA - Dewi, IGA Gangga Santi (Fakultas Hukum, Universitas Diponegoro, 2017)
The regulation of tanah bengkok is not done on the personal authority of kepala desa but is regulated in legitimate legislation, namely Undang-Undang no. 6 Tahun 2014 about Desa. Based on the results of research, tanah bengkok in Sojopuro village was given to Kepala Desa and desa apparatus as long as they served as desa apparatus and there was no legal effect if the village did not obey the rules of tanah bengkok. Therefore, a clear rule regarding the regulation of tanah bengkok is the asset of the village. Keywords: Tanah bengkok, Regulation, UU Desa.